2012
DOI: 10.1590/s0103-84782012005000015
|View full text |Cite
|
Sign up to set email alerts
|

Response of wheat to foliar application of zinc

Abstract: Wheat is grown in Brazil, mostly in no-till, a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Foliar application of urea at the later growth stages of the crop might have increased the availability of nitrogen to the crop which favoured enhanced accumulation of photosynthate in the grains. Zn, K and Ca also involve in accumulation of photosythates in the grain but to smaller extent in comparison to N. Kundu and Sarkar (2009), Zoz et al, (2012), andChaurasiya et al, (2018) also reported improvement in grain yield and yield components due to foliar spray of urea, ZnSO 4 , KNO 3 and CaCl 2 at late vegetative and reproductive stages.…”
Section: Grain Yield and Yield Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Foliar application of urea at the later growth stages of the crop might have increased the availability of nitrogen to the crop which favoured enhanced accumulation of photosynthate in the grains. Zn, K and Ca also involve in accumulation of photosythates in the grain but to smaller extent in comparison to N. Kundu and Sarkar (2009), Zoz et al, (2012), andChaurasiya et al, (2018) also reported improvement in grain yield and yield components due to foliar spray of urea, ZnSO 4 , KNO 3 and CaCl 2 at late vegetative and reproductive stages.…”
Section: Grain Yield and Yield Componentsmentioning
confidence: 99%
“…Abdi et al, (2002) reported that foliar spray of 1% potassium chloride +5% urea at double ridges and milky stages of wheat resulted significantly higher grain yield of wheat as compared to check treatment. Zinc application @ 216 g/ha at tillering and booting stage and 0.5% at tillering and grain initiation stage allowed getting 14% and 10.4% yield increment, respectively in wheat grain yield as compared to no spray (Zoz et al, 2012 andDayanand et al, 2013). Foliar application of KNO 3 (0.5% and 1.0%) and CaCl 2 (0.1%) at booting and anthesis stage improve yield under both normal as well as late sown wheat (Kang et al, 2017 andChaurasiya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The lowest volume of zinc required for wheat plants encourages the reduction of tillers primarily due to the thinning of the stem and lack of turgidity, which is considered to be the poor stem. Tillers are highly critical for their growth, sustainability or production (Davidson & Chevalier, 1990) or (Zoz et al, 2012).…”
Section: Zinc Foliar Spray On Growth and Growth Attributesmentioning
confidence: 99%
“…This can be because of the role in crop growth (Cakmak, 2008) with photosynthesized procedures, nitrogen assimilation, inhalation & start or thus their significance in the achievement of greater yield. It is worth noting that the zinc translocation added to leaves depends on the plant's nutritional status (Zoz et al, 2012).…”
Section: Zinc Foliar Spray On Yield and Yield Attributesmentioning
confidence: 99%
“…The number of spike per plant was recorded significantly maximum (6.60) under the treatment T 8 (T 4 + 0.2% foliar spray with zinc sulphate at heading stage) in comparison to other zinc fortified treatments and statistically at par with the treatments T 2 (5.87), T 6 (6.23), T 9 (6.00) and T 7 (5.96). The number of spikes was greatly affected by zinc foliar application because of the higher number of fertile tillers per plant at vegetative stage, and zinc application also reduces the weakness of the stems which further led to formation of more fertile spikes (Zoz et al 2012 andDavidson et al 1990) [31,7] .…”
Section: Number Of Spikes Per Plantmentioning
confidence: 99%